Foliar humic acid and salicylic acid application stimulates physiological responses and antioxidant systems to improve maize yield under water limitations. Issue 3 (17th February 2023) - Altaf, Adnan; Nawaz, Fahim; Majeed, Sadia; Ahsan, Muhammad; Ahmad, Khawaja Shafique; Akhtar, Gulzar; Shehzad, Muhammad Asif; Javeed, Hafiz Muhammad Rashad; Farman, Muhammad
Abstract: Background: Humic acid (HA) is an organic acid that is naturally present in soil organic matter and improves nutrient availability and the mechanisms involved in plant growth and development. Likewise, salicylic acid (SA) is an important plant hormone involved in the regulation of plant growth and development. A pot experiment was carried out to determine the effects of individual or combined HA and SA application on growth and yield of maize ( Zea mays L.) under drought stress conditions. Two maize hybrids, namely, 30T60 (drought tolerant) and 75S75 (drought sensitive), were grown in semi‐controlled conditions and foliar applied with SA (1 mM), HA (100 mg L −1 ) and their combination (HA + SA). The plants were exposed to drought stress at the tasseling stage (R1, 60 days after sowing) for 2 weeks, while control plants were given normal irrigation. Results: The results showed that HA and SA applications significantly enhanced the gas exchange characteristics (photosynthetic rate, transpiration rate, and stomatal conductance), and antioxidant activity (catalase, guaiacol peroxidase, and superoxide dismutase) of water stressed maize plants. Foliar SA spray significantly increased the photosynthetic efficiency and activity of enzymatic antioxidants closely followed by HA + SA application that ultimately improved the yield and net benefit cost ratio of maize under water deficit conditions. Conclusion: Our findings suggest that foliar spraying of SA at the initiation of the reproductive stage is a cost‐effective strategy to obtain a high maize yield under limited water conditions.